Evaluation of a continuing professional development training program for physicians and physician assistants in hospitals in Laos based on the Kirkpatrick model - Hyun Bae Yoon; Jwa-Seop Shin; Ketsomsouk Bouphavanh; Yu Min Kang (Journal of Educational Evaluation for Health Professions, 2016)
Purpose: Medical professionals from Korea and Laos have been working together to develop a continuing professional development training program covering the major clinical fields of primary care. This study aimed to evaluate the effectiveness of the program from 2013 to 2014 using the Kirkpatrick model. Methods: A questionnaire was used to evaluate the reaction of the trainees, and the trainers assessed the level of trainees’ performance at the beginning and the end of each clinical section. The transfer (behavioral change) of the trainees was evaluated through the review of medical records written by the trainees before and after the training program. Results: The trainees were satisfied with the training program, for which the average score was 4.48 out of 5.0. The average score of the trainees’ performance at the beginning was 2.39 out of 5.0, and rose to 3.88 at the end of each section. The average score of the medical records written before the training was 2.92 out of 5.0, and it rose to 3.34 after the training. The number of patient visits to the district hospitals increased. Conclusion: The continuing professional development training program, which was planned and implemented with the full engagement and responsibility of Lao health professionals, proved to be effective.